Controlled release formulation of an anti-depression drug based on a L-phenylalanate-zinc layered hydroxide intercalation compound. (June 2017) - Hashim, Norhayati; Sharif, Sharifah Norain Mohd; Isa, Illyas Md; Hamid, Shahidah Abdul; Hussein, Mohd Zobir; Bakar, Suriani Abu; Mamat, Mazidah
Abstract: The intercalation ofL -phenylalanate (LP) into the interlayer gallery of zinc layered hydroxide (ZLH) has been successfully executed using a simple direct reaction method. The synthesised intercalation compound, zinc layered hydroxide-L -phenylalanate (ZLH-LP), was characterised using PXRD, FTIR, CHNS, ICP-OES, TGA/DTG, FESEM and TEM. The PXRD patterns of the intercalation compound demonstrate an intense and symmetrical peak, indicating a well-ordered crystalline layered structure. The appearance of an intercalation peak at a low angle of 2 θ with a basal spacing of 16.3 Å, signifies the successful intercalation of theL -phenylalanate anion into the interlayer gallery of the host. The intercalation is also validated by FTIR spectroscopy and CHNS elemental analysis. Thermogravimetric analysis confirms that the ZLH-LP intercalation compound has higher thermal stability than the pristineL -phenylalanine. The observed percentage ofL -phenylalanate accumulated release varies in each release media, with 84.5%, 79.8%, 63.8% and 61.8% release in phosphate buffer saline (PBS) solution at pH 4.8, deionised water, PBS solution at pH 7.4 and NaCl solution, respectively. The release behaviour of LP from its intercalation compounds in deionised water and PBS solution at pH 4.8 follows pseudo second order, whereas in NaCl solution and PBS solution at pH 7.4, it follows the parabolic diffusion model. This study shows that the synthesised ZLH-LP intercalation compound can be used for the formation of a new generation of materials for targeted drug release with controlled release properties. Highlights: A novel ZLH-LP was synthesised via simple direct reaction method. Characterisation studies were executed using PXRD, FTIR, CHNS, ICP, TGA and FESEM. The release study of ZLH-LP was done on different human body simulated environments. The study shows potential of ZLH-LP as a new material for controlled drug release.